Tumor Necrosis Factor Alpha Level in the Uterine Fluid of Patients with Polycystic Ovary Syndrome and Its Correlation with Clinical Parameters - Ha LX; Li WX; Du YD; Yuan YY; Qu XX (Dove Medical Press, 2022)
Ling-Xia Ha,1 Wei-Xia Li,2 Yu-Dong Du,3 Ying-Ying Yuan,1 Xiao-Xiao Qu3 1Reproductive Medicine Center, General Hospital of Ningxia Medical University, Yinchuan, 750004, Ningxia, People's Republic of China; 2Reproductive Center, Maternal and Child Health Care Hospital of Yinchuan City, Yinchuan, Ningxia, 750000, People's Republic of China; 3Ningxia Medical University, General Hospital of Ningxia Medical University, Yinchuan, Ningxia, 750004, People's Republic of ChinaCorrespondence: Ling-Xia Ha, Reproductive Medicine Center, General Hospital of Ningxia Medical University, No. 804 of Shengli Road, Xingqing District, Yinchuan, Ningxia, 750004, People's Republic of China, Tel +86 951 6744033 ; +86 13629500990, Fax +86 951 6743891, Email halingxia@126.comObjective: This study aimed to analyze tumor necrosis factor alpha (TNF-α) level in the uterine fluid of patients with polycystic ovary syndrome (PCOS) and its correlation with the clinical parameters of PCOS.Methods: A total of 162 patients treated in the Reproductive Medicine Center of the General Hospital of Ningxia Medical University between December 2019 and November 2021 were enrolled as research subjects, including 80 patients with PCOS and 82 patients with other gynecological disease, who were used as the controls. The patients' general data, along with blood glucose, blood lipid, insulin, and sex hormone levels and other data, were collected. The TNF-α levels in the patients' serum and uterine fluid were detected using enzyme-linked immunosorbent assay.Results: Compared with the patients in the control group, the body mass index (BMI), anti-Müllerian hormone, luteinizing hormone, testosterone (T), fasting insulin (FINS), homeostasis model assessment insulin resistance (HOMA-IR), triglyceride (TG), and low-density lipoprotein (LDL) of patients with PCOS were higher, and high-density lipoprotein was lower (P < 0.05). The TNF-α levels in the serum and uterine fluid of patients with PCOS were higher than those in the control group (P < 0.01), and the TNF-α levels in the uterine fluid of these patients was significantly correlated with BMI, T, FINS, HOMA-IR, serum TNF-α, TG, and LDL (P < 0.05).Conclusion: There is local inflammation in the uterine cavity of patients with PCOS, and the detection of cytokines in uterine secretions may be a simple and feasible method of understanding the uterine microenvironment of patients with PCOS.Keywords: polycystic ovary syndrome, uterine fluid, TNF-α, insulin resistance, lipid metabolism